2022
DOI: 10.3389/fphar.2022.824138
|View full text |Cite
|
Sign up to set email alerts
|

Cajaninstilbene Acid Ameliorates Acetaminophen-Induced Liver Injury Through Enhancing Sestrin2/AMPK-Mediated Mitochondrial Quality Control

Abstract: Acetaminophen (APAP)-induced liver injury (AILI) is the main cause of acute liver failure in the developed countries. The present study aimed to evaluate the therapeutic efficacy of cajaninstilbene acid (CSA), a major stilbene compound derived from the leaves of pigeon pea [Cajanus cajan (L.) Millsp.], against AILI. CSA (50, 75 mg/kg, p. o.) was administered to male C57BL/6 N mice 0.5 h after a toxic dose of APAP (300 mg/kg, i. p.). The direct effect of CSA on hepatocytes was tested on primary mouse hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Although it is not clear the reason behind this contrast, it is well established that hepatotoxicants can induce different responses of the cytoprotective modulator. In a previous study by Yan et al [ 64 ], the expression level of PGC-1α decreased when detected at 6 h after APAP overdose, suggesting that mitochondrial biogenesis is disturbed by APAP at this time point. On the other hand, the study by Goldring et al [ 65 ] reported that APAP activates Nrf2 to some extent in mouse liver following administration of non-hepatotoxic and hepatotoxic doses, implying that Nrf2 has a sudden response effect against APAP administration.…”
Section: Discussionmentioning
confidence: 84%
“…Although it is not clear the reason behind this contrast, it is well established that hepatotoxicants can induce different responses of the cytoprotective modulator. In a previous study by Yan et al [ 64 ], the expression level of PGC-1α decreased when detected at 6 h after APAP overdose, suggesting that mitochondrial biogenesis is disturbed by APAP at this time point. On the other hand, the study by Goldring et al [ 65 ] reported that APAP activates Nrf2 to some extent in mouse liver following administration of non-hepatotoxic and hepatotoxic doses, implying that Nrf2 has a sudden response effect against APAP administration.…”
Section: Discussionmentioning
confidence: 84%
“…Peroxisome proliferator-activated receptor γ-coactivator 1α (PGC-1α) is an important regulator of mitochondrial biogenesis [ 27 ] that controls a series of downstream targets, including NRF1 and TFAM. With excessive APAP, PGC-1 α expression is decreased [ 46 ]. Our results showed that the expression of PGC1-α, NRF1 and TFAM decreased after APAP intervention compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating standardization and herb identification is essential to implementing efficient quality control procedures. Establishing constant and dependable concentrations of active ingredients or indicators in herbal medicine products is the first step toward standardizing and identifying herbs (Wang et al, 2023). This may entail methods like particular chemical assays, spectroscopy (UV-Vis, IR), or chromatography (HPLC, GC) (Chen et al, 2023).…”
Section: Future Implicationsmentioning
confidence: 99%